Penguatan Skill Listening dan Vocabulary di MTs Terpadu Berkah Palangka Raya melalui lagu One Call Away oleh Charlie Puth - Alya Audria; Ayu Sundari; Fatma Fatma; Rizki Hasanah; Mayra Musdalifah; Siti Rahmawati; Kholida Ziya; Abdul Syahid (Universitas Maritim AMNI Semarang, 2024)
This article examines community service efforts aimed at strengthening listening skills and expanding vocabulary among students at MTs Integrated Berkah Palangka Raya through an innovative approach using Charlie Puth's song